Cataract risk in US radiologic technologists assisting with fluoroscopically guided interventional procedures: a retrospective cohort study. Issue 5 (19th March 2019) - Velazquez-Kronen, Raquel; Borrego, David; Gilbert, Ethel S; Miller, Donald L; Moysich, Kirsten B; Freudenheim, Jo L; Wactawski-Wende, Jean; Cahoon, Elizabeth K; Little, Mark P; Millen, Amy E; Balter, Stephen; Alexander, Bruce H; et al.
Abstract : Objectives: To assess radiation exposure-related work history and risk of cataract and cataract surgery among radiologic technologists assisting with fluoroscopically guided interventional procedures (FGIP). Methods: This retrospective study included 35 751 radiologic technologists who reported being cataract-free at baseline (1994–1998) and completed a follow-up questionnaire (2013–2014). Frequencies of assisting with 21 types of FGIP and use of radiation protection equipment during five time periods (before 1970, 1970–1979, 1980–1989, 1990–1999, 2000–2009) were derived from an additional self-administered questionnaire in 2013–2014. Multivariable-adjusted relative risks (RRs) for self-reported cataract diagnosis and cataract surgery were estimated according to FGIP work history. Results: During follow-up, 9372 technologists reported incident physician-diagnosed cataract; 4278 of incident cases reported undergoing cataract surgery. Technologists who ever assisted with FGIP had increased risk for cataract compared with those who never assisted with FGIP (RR: 1.18, 95% CI 1.11 to 1.25). Risk increased with increasing cumulative number of FGIP; the RR for technologists who assisted with >5000 FGIP compared with those who never assisted was 1.38 (95% CI 1.24 to 1.53; p trend <0.001). These associations were more pronounced for FGIP when technologists were located ≤3 feet (≤0.9 m) from the patient compared with >3 feet (>0.9 m) (RRs for >5000 at ≤3 feet vs never FGIP were 1.48, 95% CI 1.27 to 1.74 and 1.15, 95% CI 0.98 to 1.35, respectively; pdifference=0.04). Similar risks, although not statistically significant, were observed for cataract surgery. Conclusion: Technologists who reported assisting with FGIP, particularly high-volume FGIP within 3 feet of the patient, had increased risk of incident cataract. Additional investigation should evaluate estimated dose response and medically validated cataract type.